Environmental hazards : assessing risk and reducing disaster - Smith, Keith, 1938-; Fearnley, Carina J.; Kelman, Ilan; Dixon, Deborah P.; Bird, Deanne K. (Routledge, 2024)
"The seventh edition of Environmental Hazards provides a much expanded and fully up-to-date overview of all the extreme environmental events that threaten people and what they value in the 21st century globally. It integrates cutting-edge materials to provide an interdisciplinary approach to environmental hazards and their management, illustrating how natural and human systems interact to place communities of all sizes, and at all stages of economic development, at risk. Part One defines basic concepts of hazard, risk, vulnerability and disaster and explores the evolution of hazards theory. Part Two employs a consistent chapter structure to demonstrate how individual hazards occur, their impacts, and how the risks can be assessed and managed. This carefully structured and balanced textbook captures the complexity and dynamism of environmental hazards and is essential reading for students across many disciplines including Geography, Environmental Science, Environmental Studies and Natural Resources"--